The Role of PATRIA Bulletin in Information Dissemination at PT United Tractors Pandu Engineering - Citra Ayu Shafinas; Guruh Ramdani (Jurnal Komunikasi Nusantara, 2026)
PATRIA Bulletin is a digital internal communication medium created by PT United Tractors Pandu Engineering to support the dissemination of organizational information, strengthen corporate culture, and enhance employee engagement across divisions. As the company continues its digital transformation, the Bulletin plays an important role in ensuring that key messages, corporate values, achievements, and development programs are delivered to employees in a clear and structured manner. The uniqueness of this study lies in its focus on communication patterns and message construction within the Bulletin’s production process, an area rarely explored in previous research. This study examines how PATRIA Bulletin functions as an information channel, the types of messages conveyed, interdivision communication, and digital engagement. Using a qualitative study approach, the research draws on interviews, observations, and digital analysis. The findings indicate that effective communication patterns are essential for strengthening PATRIA Bulletin as a sustainable internal medium. Abstrak PATRIA Bulletin adalah media komunikasi internal digital yang dibuat oleh PT United Tractors Pandu Engineering untuk mendukung penyebaran informasi organisasi, memperkuat budaya perusahaan, dan meningkatkan keterlibatan karyawan di seluruh divisi. Seiring perusahaan melanjutkan transformasi digitalnya, Bulletin berperan penting dalam memastikan pesan utama, nilai perusahaan, pencapaian, dan program pengembangan tersampaikan kepada karyawan secara jelas dan terstruktur. Keunikan penelitian ini terletak pada fokusnya terhadap pola komunikasi dan konstruksi pesan dalam proses produksi Bulletin, area yang jarang dieksplorasi dalam penelitian sebelumnya. Penelitian ini menelaah bagaimana PATRIA Bulletin berfungsi sebagai saluran informasi, jenis pesan yang disampaikan, komunikasi antardivisi, dan keterlibatan digital. Dengan menggunakan pendekatan studi kualitatif, penelitian ini mengacu pada wawancara, observasi, dan analisis digital. Temuan menunjukkan bahwa pola komunikasi yang efektif sangat penting untuk memperkuat PATRIA Bulletin sebagai media internal yang berkelanjutan.